Full-Time Schooling in Life-Cycle Models of Human Capital Accumulation - Wallace, T. D.; Ihnen, L. A. (Journal of Political Economy, 1975)
A reduced-form equation relating length of "formal schooling" to market, endowment, and ability parameters was derived for a life-cycle human capital accumulation model with alternative assumptions: (a) equal borrowing and lending rates and (b) no loans for human capital investment. Length of "formal schooling" increases when loans are unavailable. For both cases, length of "formal schooling" varies directly with length of work life, a Hicks-neutral "ability" index, and the ratio of the human capital rental rate to the price of associated inputs, and varies inversely with the discount rate, deterioration rate, and initial human capital stock.